2014
DOI: 10.1155/2014/369204
|View full text |Cite
|
Sign up to set email alerts
|

Jatropha gossypiifolia L. (Euphorbiaceae): A Review of Traditional Uses, Phytochemistry, Pharmacology, and Toxicology of This Medicinal Plant

Abstract: Jatropha gossypiifolia L. (Euphorbiaceae), widely known as “bellyache bush,” is a medicinal plant largely used throughout Africa and America. Several human and veterinary uses in traditional medicine are described for different parts and preparations based on this plant. However, critical reviews discussing emphatically its medicinal value are missing. This review aims to provide an up-to-date overview of the traditional uses, as well as the phytochemistry, pharmacology, and toxicity data of J. gossypiifolia s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 110 publications
1
50
2
3
Order By: Relevance
“…This suggests that J. curcas with J. stevensii and J. costaricensis could have a common ancestor and more distant J. gossypifolia. This is consistent with the reports that point J. curcas, J. integerrima, J. glandulifera, and J. gossypifolia as native from America, and that they have been introduced to tropical countries in Africa and South East Asia (Indian, Indonesia, Malaysia and China) [30] [31] [34] [35].…”
Section: Genetic Relationships Of Jatropha Populationssupporting
confidence: 91%
“…This suggests that J. curcas with J. stevensii and J. costaricensis could have a common ancestor and more distant J. gossypifolia. This is consistent with the reports that point J. curcas, J. integerrima, J. glandulifera, and J. gossypifolia as native from America, and that they have been introduced to tropical countries in Africa and South East Asia (Indian, Indonesia, Malaysia and China) [30] [31] [34] [35].…”
Section: Genetic Relationships Of Jatropha Populationssupporting
confidence: 91%
“…Although, J. gossypiifolia is considered an important plant with potential for the generation of pharmacological and/or biotechnological products (Félix-Silva et al, 2014), the assays performed in this study indicated cytotoxicity, genotoxicity, and/or mutagenicity at the chromosome level for all the tested concentrations of the ethanolic leaf extract and for the concentrations 0.01 mg/mL or above, of the aqueous leaf extract of J. gossypiifolia, particularly for the three highest concentrations. This alerts us to the eventual possibility of J. gossypiifolia leaf extracts posing risk to human health, even though they possess various medicinal applications.…”
Section: Discussionmentioning
confidence: 52%
“…The phytochemical profile of the ethanolic extract of J. gossypiifolia has revealed the presence of steroids, phenols, tannins, saponins, oils, monoterpenes, diterpenes, triterpenes, and sesquiterpenes in the stem, leaves, and roots (Mariz et al, 2010;Devappa et al, 2011;Sabandar et al, 2013). However, phytochemical evaluations of aqueous extracts are still incipient, even though the plant is popularly used in the form of an infusion or decoction (Félix-Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jatropha species are used in folk medicine to treat various diseases, such as skin inflammation, eye infection, chest pain, stomach pain, itching, and as a vermifuge or as ornamental plants and energy crops in Latin America, Africa, and Asia [3]. Several known species from the genus Jatropha, such as J. gossypiifolia, J. elliptica, J. curcas, and J. mollissima, among others, have been reported for their chemical constituents, biological activities, and medicinal uses [4].…”
Section: Introductionmentioning
confidence: 99%